Representation of Expressive Speech Acts in the WebSeries 17 Selamanya: A Case Study in Pragmatic Analysis - Khoif, Moh Annur; Rokhman, Fathur (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2025)
This study aims to identify the types of expressive speech acts, analyze their functions, and interpret their meanings in the Indonesian web series '17 Forever'. Using a qualitative descriptive approach, the research analyzes dialogue fragments collected through the listening method and categorized based on type, function, and meaning. The findings reveal eight types of expressive speech acts, including direct, indirect, literal, and non-literal variations. Ten functions were identified, such as praising, complimenting, complaining, congratulating, saying thank you, blaming, apologizing, expressing anger, expressing sadness, showing sympathy, and mocking. Additionally, the analysis uncovered ten meanings, including insulting, praising, complaining, congratulating, saying thank you, blaming, apologizing, expressing anger, expressing sadness, showing sympathy, and mocking. This research contributes to a deeper understanding of expressive speech acts in Indonesian web series and provides a foundation for future studies in similar contexts.